Prospection, Collecte, Nomenclature Paysanne Et Caracterisation Des Variables Qualitatives Des Varietes Locales De Maïs (Zea Mays L.) Cultivees En Cote d’Ivoire - Annicet N’da, Hugues; Akanvou, Louise; Bi Zoro, Arsène Irié (European Scientific Journal, ESJ, 2016)
Ivoirian landraces of maize were maintained for several centuries in different ecological conditions, which allowed them to accumulate a large genetic diversity yet little studied. This study aims to make a first inventory of the existing diversity and establish a representative collection of the diversity of this crop in Côte d’Ivoire. Surveys and collection of maize landraces were conducted in three agro-ecological zones of Côte d’Ivoire. Two hundred and forty seven villages were selected and prospect in twentyfour regions. In each village, passport data were collected using the tools and methods of participatory research. A sample of 829 maize accessions were collected. The preliminary characterization of this collection was performed based on the descriptors of maize developed by Bioversity International. The study revealed a significant varietal diversity. Five varieties have been identified based on the color of the grains: yellow maize, white maize, red maize, purple maize and variegated maize. Varieties with yellow grain, with a percentage of 54.16% have been the most prevalent in different areas surveyed. Varieties with purple and red grain have been rare, with respective numbers of 3.38 and 3.62%. Interviews conducted with producers have permitted to inventory 81 local names. The main criteria of farmers to characterize local ecotypes was grains color. The collected accessions are an important gene pool for the present and future generations in the context of plant breeding work.